3 - The Scramble for the Partition of the Northern Region of Ghana: Conflict and the Quest for the Coterminality of Cultural and Political Boundaries - M. H. A. Bolaji,; Mohammed Adam Gariba, (African Sociological Review, 2020)
The Northern Region was not only the largest administrative region in Ghana, but it was also almost one-third of the landmass of Ghana. Since 1960 there have been calls from various constituencies for it to be split into two or more manageable regions for rapid development. Eventually, the New Patriotic Party’s (NPP) government put in place mechanisms to create new regions out of three – including the Northern Region – of the existing ten regions. As the Commission of Inquiry (CoI) began its consultations with the traditional authorities and other stakeholders, a scramble ensued between two kingdoms in the then Northern Region to ensure that their cultural boundaries were coterminous with the political boundaries of the regions to be created. Thispaper disseminates the findin s of a qualitative research work that took place between October 2017 and June 2018 in the then Northern Region, Ghana. TheresearchaimedatinvestigatingthepoliticsandconflictsthataccompaniedDagbon’s and Gonja’s claim of non-cession of their territories to the new regions to be created. After establishing the interconnectedness between territory, sovereignty, and identity, the study unearths how the Dagbon chieftaincy conflict shaped the various perspectives on the regional reorganization (RR) in Dagbon and how the regional reorganization (RR) revitalized the minority question in Gonjaland. Drawing on internal self-determination, it concludes with a note that underscores the importance of kingdoms when it comes to territories and their demarcations in modern states in Africa.